What color is your parachute? for teens : discover yourself, design your future, and plan for your dream job - Christen, Carol; Bolles, Richard Nelson (Ten Speed Press, 2015)
This updated career guide for teens draws on the principles of "What Color Is Your Parachute?" to help high school and college students zero in on their favorite skills and find their perfect major or career.